Financial Reporting Discretion, Managerial Myopia, and Investment Efficiency - Jiang, Xu; Xin, Baohua (The Accounting Review, 2022)
ABSTRACT We explicitly model financial reporting discretion and earnings management in an investment setting where managers have incentives to behave myopically. We show that when managers are sufficiently, but not excessively, myopic, granting them some discretion over the mandatory financial reports can lead to better investment decisions. This finding contrasts with the conventional argument that financial reporting discretion facilitates earnings management and exacerbates managerial myopia, leading to inefficient investments. Costly earnings management, while offering managers some ex post protection against bad luck by decreasing the incidence of low financial reports, reduces the expected net benefit of high financial reports ex ante. Consequently, managers with negative private information find it too costly to mimic those with positive private information, facilitating separation of managers through efficient investment. Thus, curbing managerial myopia by removing or overly restricting earnings management may have the unintended consequence of impairing investment efficiency.